2023
DOI: 10.3389/fimmu.2023.1089622
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the shared pathways and common biomarker PAN3 in ankylosing spondylitis and ulcerative colitis using integrated bioinformatics analysis

Abstract: BackgroundUlcerative colitis (UC) is a chronic autoimmune-related disease that causes inflammation of the intestine. Ankylosing spondylitis (AS) is a common extraintestinal complication of UC involving the sacroiliac joint. However, the pathogenesis of AS secondary to UC has not been studied. This study aimed to investigate the shared pathways and potential common biomarkers of UC and AS.MethodsMicroarray data downloaded from the Gene Expression Omnibus (GEO) database were used to screen differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have shown that T lymphocyte abnormalities play an important role in endothelial cell dysfunction 35 . The study Zhang et al showed elevated levels of CD8 + T lymphocytes in patients with OSA compared to controls 16 and that activated CD8 + T lymphocytes can have a killing effect on vascular endothelial cells, thus aiding the progression of secondary atherosclerosis. Atherosclerosis is a chronic inflammatory disease with immune infiltration 36 , and Patients with atherosclerosis have significantly elevated CD8 T cells 37 , mainly in the fibrous cap area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that T lymphocyte abnormalities play an important role in endothelial cell dysfunction 35 . The study Zhang et al showed elevated levels of CD8 + T lymphocytes in patients with OSA compared to controls 16 and that activated CD8 + T lymphocytes can have a killing effect on vascular endothelial cells, thus aiding the progression of secondary atherosclerosis. Atherosclerosis is a chronic inflammatory disease with immune infiltration 36 , and Patients with atherosclerosis have significantly elevated CD8 T cells 37 , mainly in the fibrous cap area.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we collected data from the GEO database, then screened for differential genes, performed enrichment analysis, WGCNA analysis, Gene Set Enrichment Analysis (GSEA) analysis 14 , and LASSO 15 regression models to screen for shared pathways and key biomarkers for OSA and AS, and analyzed the expression levels and diagnostic value of the genes, validated the dataset for validation, and examined monocytes from blood samples collected from patients. By these similar methods, Zhang et al 16 found that the MAPK signaling pathway may be associated with both pathogenesis of ankylosing spondylitis and ulcerative colitis and that poly(A) specific ribonuclease subunit PAN3 Gene (PAN3) may be a potential diagnostic marker for patients with ulcerative colitis complicated by ankylosing spondylitis. Similarly, Gao 17 used these similar approaches to find that immune responses may be associated with both epilepsy and subarachnoid hemorrhage pathogenesis and that Matrix metalloproteinase-9 (MMP9) and Complement C3a Receptor 1 (C3aR1) may be potential diagnostic markers for subarachnoid hemorrhage complicated by epilepsy.…”
mentioning
confidence: 99%
“…Integration events in PAN3, BABAM2, and SPEN were detected in both tumor and normal cells, each gene expression showing signi cant difference in terms of the ratio of cells containing the integrations in that gene (p < 2.2e − 16, χ² test). It was reported that PAN3 was closely related to pancreatic cancer [40], previously linked to pancreatic cancer and acute lymphoblastic leukemia [41], was identi ed as a biomarker gene in ulcerative colitis in recent research [42], and BABAM2 was found to form a novel BABAM2-ALK fusion, potentially contributing to the pathogenesis of a small subset of gynecologic clear cell carcinomas [43]. SPEN, known for its high mutational frequency variety in mantle cell lymphoma [44], was the only highfrequency-cell gene that exhibited signi cant differences on gene expression between cells with and without integration.…”
Section: The Distribution Of Hpv-integrated Genes Across Disease Stag...mentioning
confidence: 99%
“…Furthermore, Pearson's correlation test was applied to calculate the correlation between ME and clinical features. The modules with a |ME| > 0.3 and a p-value <0.05 were deemed to have significant interactions with clinical features (Zhang et al, 2023).…”
Section: Weighted Gene Coexpression Network Analysis (Wgcna)mentioning
confidence: 99%